Identification of Family Medicinal Plants in Bulusari Village, Wonogiri as High School Biology Learning Resources - Agus Purwanto; Muthia Mardyah (Jurnal Biologi Tropis, 2026)
The diversity of family medicinal plants in Indonesia represents an important biological resource that supports public health and has considerable potential as a learning resource in biology; however, it has not been optimally utilized in senior high school biodiversity education. This study aims to identify medicinal plant species in Bulusari Village, analyze their distribution, and evaluate their potential as a biology learning resource based on local wisdom. The study employed an exploratory descriptive method with direct field observation and semi-structured interviews. Data collection was conducted using a total sampling technique, in which all medicinal plant species found in home gardens and surrounding village environments were recorded and identified. Data were analyzed descriptively based on botanical classification, distribution patterns, and medicinal uses. The results identified 25 medicinal plant species belonging to 19 families and 6 classes, with Asteraceae as the dominant family. The plants were distributed across cultivated home gardens and wild habitats. These findings indicate that the diversity of family medicinal plants in Bulusari Village has strong potential as a contextual biology learning resource for senior high school, supporting authentic, environment-based, and locally relevant learning.